Perkembangan Makna Bahasa Arab - Nelis Jamilah Ilmiatun (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2022)
Arabic is a language rich in meaning, the richness of meaning of each sentence makes Arabic the language of literature and science. Each word in Arabic can be interpreted with more than one meaning. And Every meaning of an Arabic sentence can change the form by adding meaning, reducing meaning, or changing the structure of the form of the sentence. The nature of the change is a sign of the dynamism of a language resulting from human culture. The development of the meaning of Arabic is due to the existence of Language change as a necessity for the development of thinking, science, and the state of the human being in situations and conditions when interacting that are unlikely to be in the same state. And other factors that cause such changes occur in all linguistic structures of the Arabic language namely phonology, morphology, syntax, semantics and lexicon.